Sistem Pendukung Keputusan Pemilihan Supplier Bahan Mentah Dengan Metode Weighted Product - Nur Falah Muhammad; Fattya Ariani (Jurnal Teknik Komputer AMIK BSI, 2022)
Supplier is one of the important things in the company. Inappropriate supplier selection will hamper the running business process. CV. Kitchen Radita in the selection of suppliers is still a subjective assessment. The selection of suppliers in this way causes several problems such as delays in the delivery of raw materials, poor quality of goods and so on. CV. Kitchen Radita needs a solution to overcome the problem of supplier selection. With these problems, a supplier selection decision support system is needed to help companies produce the best suppliers. This study uses the Weighted Product (WP) method. This method uses multiplication to connect attribute ratings, where the rating must be raised to the first rank with the weight of the attribute in question. With an assessment of four criteria, namely quality, price, estimated delivery and consistency. There are ten suppliers that are used as alternatives. The results of this study the criteria with the highest weight is quality. And supplier A5 gets the highest preference weight value of 0.108722647 taken from the highest rank. With the existence of a supplier selection decision support system using the Weighted Product (WP) method, it helps companies in selecting the right supplier.